Recognizing the development of socio-discursive skills in the university (Ágora de Heterodoxias, 2016)
This article is an updated version of the paper Development of socio-discursive competencies in the college classroom presented in the "XII International Congress of Organizational Analysis" in 2014, and the purpose is to address comments received for theoretical adequacy and some evidence relating the way that development of socio-discursive skills in the university classroom is recognized, by mediated interaction with computerized communication devices during the process of teaching and learning, but without focusing therefore in such process and identifying it as the moment in which the interaction occurs. For this, the methodological approach includes a design of an experiment that explores the temporal sequences of interaction mediated with computerized communication devices used in the processes of teaching and learning in different educational programs, recording the socio-discursive skills that occur in Cozumel Academic Unit of the University of Quintana Roo by the initiation-response-evaluation sequence (IRE), recognizing how this IRE sequence occurs during the speeches given in the room, discarding those competencies that are not related to the use of the devices. The gathered information observed by using the IRE sequence was performed under the precepts of classroom observation, methodological proposal that up to now confirm us the hypothesis that the socio-discursive skills are developed in interaction and not by learning, thereby allowing to theorize this linguistic practice from the public organization.
Keywords: organizational studies; school organization; literacy; socio-discursive skills; research results